Motivation and Challenges of Woman Entrepreneurs in the Digital Era (Case Study of Women Entrepreneur in Bandung) - Putri, Mediany Kriseka; Shodiq, Rhakel Muliah (Publikasi Inspirasi Indonesia, 2024)
Indonesia, with its large population, has strong potential to advance its economy through entrepreneurship, especially in the digital era. The digital economy is crucial in promoting the progress of Micro, Small, and Medium Enterprises (MSMEs). It also drives societal changes, particularly by encouraging women's active participation in economic development through entrepreneurship. The research aims to identify the dominant factors driving women into entrepreneurship and the obstacles they encounter. Using a qualitative methodology, including interviews with 9 woman entrepreneurs and document analysis, the study found that pull factors—such as the desire for autonomy, higher earnings, and broader market opportunities—are the primary motivations for woman entrepreneurs, while challenges in digital technology and marketing skills significantly hinder their success. The study suggests that government and community support is essential to address these challenges and foster the growth of women entrepreneurs in the digital economy, offering important insights and recommendations for empowering this demographic.